Spike fertility and duration of stem elongation as promising traits to improve potential grain number (and yield): Variation in modern Argentinean wheats - González, Fernanda Gabriela (2011)
The identification of physiological traits that determine grain number (and yield) in modern cultivars, and the possible tradeoffs among them, may help to detect promising traits for breeding to increase yield potential. High-yielding Argentinean wheat (Triticum aestivum L.) cultivars were grown under irrigated and highinput conditions during two seasons to study (i) yield and grain number m-2 (GN) as a result of stover biomass at harvest (SH) and harvest index (HI); and (ii) spike dry weight at anthesis (SDWa; g m-2) and spike fertility index (SFI; grain number per gram of spike chaffor non-grain spike biomass). Duration of the stem elongation phase (SEP; first node detectable to anthesis) was analyzed as an alternative to increase SDWa. The HI was highly associated with yield differences between cultivars for both years, independently of stem height. In contrast, SH did not vary among cultivars in either season (P > 0.05). The GN determined yield differences between cultivars and was highly associated with SFIand SDWa for both years and cycles. Some cultivars with the same anthesis date showed stable variation for duration of the SEP between years (despite the year × cultivar interaction observed). As the SFIand duration of the SEP were not related, it seems promising to increase GN in a cultivar with high SFIthrough an increased duration of the SEP (which may yield higher SWDa) or vice versa.